Manusia yang Beradab Menurut Tri Kaya Parisudha - Felix Mahendra (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
The focus of this study aims to explore the deepest meaning of civilized humanity in the second principle of Pancasila, namely